High dielectric performance and multifarious polarizations in (Lu + Ta) co-doped TiO2 ceramics. Issue 3 (3rd July 2021) - Fan, Jiangtao; Long, Zhen; Hu, Zhanggui
ABSTRACT: Materials with high dielectric constant have broad application prospects in energy storage elements. In this work, (Lu0.5 Ta0.5 )x Ti1-x O2 ceramics (x = 0, 0.01, 0.02 and 0.04) were synthesized by a standard conventional solid-state reaction. Remarkably, (Lu0.5 Ta0.5 )0.01 Ti0.99 O2 ceramic exhibits a high dielectric permittivity (2.55 × 10 4 ), low dielectric loss (0.012) and excellent stabilities of frequency and temperature (−150–150°C and 20–5 × 10 6 Hz). The formation mechanism of excellent dielectric properties was studied based on analysis of the XRD, SEM, XPS, complex impedance and electric modulus. Colossal permittivity (CP) and low tan δ were attributed to the internal barrier layer capacitance (IBLC) effect, electron-pinned defect-dipole (EPDD) effect and electrode effect. This work has important guidance for the further research of giant dielectric materials.